Acoustic emission investigation of coal gangue cementitious composites under effects on fiber type. (December 2022) - He, Zequan; Ju, Feng; Ning, Pai; Xiao, Meng; Wang, Tengfei; Wang, Dong
Abstract: A material known as coal gangue cementitious composite (CGCC), which is made of coal gangue, cement, and additives among other things, is frequently used in the field of coal backfilling mining to regulate the stability of surrounding rock and protect the environment. Due to the strict criteria for high performance of CGCC under the unique operating conditions in mining, it has been widely discussed to increase CGCC performance by adding fibers. In the absence of relevant basic research, fiber insertion results in significant differences in microstructure and mechanical failure behavior between materials and standard CGCC. The CGCCs with CF and SF were subjected to a uniaxial compression acoustic emission test in this study, and the samples' mechanical deformation characteristics and acoustic emission parameters were measured during the loading procedure. To compare and contrast CGCCs made of various fiber types, mechanical properties, fracture evolution laws, and acoustic emission characteristics are used. According to the findings, addition of fibers and the increase of curing age have a positive effect on improving the mechanical properties, and rate of maximum compressive strength was 25.0%. According to the analysis of AE parameter method, the existence of fibers has a positive impact on the on the ability to resist tensile failure of CGCC, leading to the transformation of structural damage from tensile crack to shear crack. Furthermore, as curing age increases, the development of shear cracks in the sample deepens, resulting in an increase in the proportion of AF:RA< 1 of up to 4.97 %. This paper proposes new ideas for promoting the development of environmentally friendly composite materials and realizing the multi-functional use of CGCCs.